PENGARUH PENGHAYATAN NILAI-NILAI SPIRITUALITAS SFS TERHADAP PELAYANAN PARA GURU SD ST. FRANSISKUS ASSISI, SRAGEN - Mandonsa, Maria Raineldis; Wilhelmus, Ola Rongan (CREDENDUM: Jurnal Pendidikan Agama, 2022)
The results of observations, that reseaechers has done, show that the majority of teachers still prioritize the formation of cognitive abilities in students rather than instill the spiritual values such as brotherhood, love, repentance, prayer, service and simplicity.The results of this field observation encourage the researcher to do the scientific research with the title: The comprehension and Appreciantion of the Elementary School Teachers of St. Francis of Assisi, Sragen Towards the Spirituality of the SFS Cogregation. This research aims to obtain a deep understanding of the teachers of SD St. Fransiskus Assisi, about the essence of Christian Spirituality and SFS spirituality; analize in what extent the teachers of Elementary School of Francis of Assisi, live their life based on the spirituality of SFS; and analyze the impact of SFS spirituality on the behavior and the work of the teachers’ daily life at St. Elementary School of Francis of Assisi, Sragen. The results of the analysis, based on research data, show that most respondents think that SFS spirituality is seen as a spirituality that emphasizes love, repentance, prayer, service, brotherhood and simplicity.